Penerapan Hukum dalam Menangani Kasus Korupsi di Sekolah: Perspekif Sosiologi Tentang Dampak dan Solusi - khairunisa, Yasmin; Mulyana, Aji; Amalia, Mia (Indonesian Journal Publisher, 2024)
This study examines the application of law in addressing corruption cases within schools from a sociological perspective, focusing on their impacts and solutions. Corruption in the education sector leads to significant societal and state losses, with primary causes including weak oversight from the Ministry of Education and related institutions. The research employs a normative juridical method, emphasizing legal norms to analyze the role of law in combating corruption in educational environments. The findings reveal a continuous rise in corruption cases in Indonesian schools, adversely affecting education quality, creating inequities in access to education, and eroding public trust in educational institutions. Identified contributing factors include insufficient supervision, lack of transparency in fund management, economic pressures, and a permissive culture toward corrupt practices. To address these issues, preventive measures such as enhancing financial transparency, strengthening oversight through school committees and independent bodies, and integrating anti-corruption education into curricula are essential. Cooperation with anti-corruption agencies and public engagement in monitoring efforts further support these initiatives. Effective regulation and enforcement, coupled with a commitment to integrity, are critical to fostering a corruption-free educational environment. This study underscores the importance of comprehensive and collaborative strategies in promoting transparency and accountability within the education sector.